PERLINDUNGAN HUKUM HAK CIPTA SENI PATUNG DI KABUPATEN MAGELANG DALAM PERSPEKTIF PENGETAHUAN TRADISIONAL DAN EKSPRESI BUDAYA - RANI PAJRIN; RR YUNITA PUSPANDARI; ABDUL AZIS (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The issue of legal protection for culture, traditional knowledge needs to be a concern for all parties, both from society and government. Law Number 5 of 2017 concerning the Advancement of Culture in which efforts to promote, protect, develop, utilize and foster culture need to be carried out in all aspects of culture. Copyright is an individual nature, while traditional knowledge (culture) is communal in nature and is shared ownership. The role of local government in legal protection efforts for works of a traditional nature, especially sculpture in the Magelang regency, is quite central. The research method used by the author is socio legal research where law is a social phenomenon. Legal protection carried out by the Magelang regency government is to conduct an inventory of cultural heritage objects in the Magelang Regency area. These cultural heritage objects certainly have potential intellectual property rights. Not yet optimal legal protection carried out by the Regional Government of Magelang Regency, both for art workers and works made (cultural heritage objects) in the context of cultural advancement, it is necessary to have Regional Regulations that technically regulate protection, development, empowerment, preservation, security as well as salvaging traditional works of art that have the prospect of intellectual property rights.